Motor imagery and sport performance - Nobuaki Mizuguchi; Hiroki Nakata; Yusuke Uchida; Kazuyuki Kanosue (Japanese Society of Physical Fitness and Sports Medicine, 2012)
In the present review, how to measure motor imagery ability, brain activity during motor imagery, the benefits of motor imagery practice, and the influence of sensory inputs on motor imagery, are summarized. First, the classification of motor imagery is explained. Many methods have been utilized to evaluate motor imagery ability. For example, questionnaires, mental chronometry, and mental rotation tasks have been used in the psychological approach. Brain activity has been measured utilizing transcranial magnetic stimulation (TMS), functional magnetic resonance imaging (fMRI), positron emission tomography (PET), and electroencephalography (EEG). Some brain regions are activated motor execution in both and motor imagery, including the supplementary motor area (SMA), the premotor cortex (PM) and the parietal cortex. Although motor imagery is done without movement or muscle contraction, sensory input from the periphery interacts with motor imagery. Brain activation during imagery of an action, as assessed by TMS, is stronger when sensory inputs resemble those present during the actual execution of the action. Many studies have provided evidence of the effects of motor imagery practice on basic motor skills and sport performance. Most elite athletes (70-90%) report that they use motor imagery to improve performance, and professional players, as compared to amateurs, utilize imagery practice more often. Many studies have confirmed that motor imagery practice can also be useful not only in sports, but also for improving performance in patient rehabilitation programs.